The Arf GAP SMAP2 is Necessary for Organized Vesicle Budding from the Trans-Golgi-network and Subsequent Acrosome Formation in Spermiogenesis - Funaki, T.; Kon, S.; Tanabe, K.; Natsume, W.; Sato, S.; Shimizu, T.; Yoshida, N.; Wong, W.F.; Ogura, A.; Ogawa, T.; Inoue, K.; Ogonuki, N.; et al. (American Society for Cell Biology, 2013)
The trans-Golgi-network (TGN) functions as a hub organelle in the exocytosis of clathrin-coated membrane vesicles, and SMAP2 is an Arf GTPase activating protein that binds to both clathrin and the clathrin assembly protein (CALM). In the present study, SMAP2 was detected on the TGN in the pachytene spermatocyte to the round spermatid stages of spermatogenesis. Gene targeting revealed that SMAP2-deficient male mice were healthy and survived to adulthood, but were infertile and exhibited globozoospermia. In SMAP2-deficient spermatids, the diameter of proacrosomal vesicles budding from TGN increased, TGN structures were distorted, acrosome formation was severely impaired, and reorganization of the nucleus did not proceed properly. CALM functions to regulate vesicle sizes, and this study showed that CALM was not recruited to the TGN in the absence of SMAP2. Furthermore, syntaxin2, a component of the SNARE complex, was not properly concentrated at the site of acrosome formation. Thus, the present study reveals a link between SMAP2 and CALM/syntaxin2 in clathrin-coated vesicle formation from the TGN and subsequent acrosome formation. SMAP2-deficient mice provide a model for globozoospermia in humans.